Novel role for tumor suppressor gene, liver kinase B1, in epithelial–mesenchymal transition leading to chronic lung allograft dysfunction. Issue 3 (16th December 2021) - Rahman, Mohammad; Ravichandran, Ranjithkumar; Bansal, Sandhya; Sanborn, Kristina; Bowen, Sara; Eschbacher, Jennifer; Sureshbabu, Angara; Fleming, Timothy; Bharat, Ankit; Walia, Rajat; Hachem, Ramsey; Bremner, Ross M.; et al.
Abstract : Epithelial–mesenchymal transition (EMT) has been implicated to play a role in chronic lung allograft dysfunction (CLAD). Liver kinase B1 (LKB1), a tumor suppressor gene, can regulate EMT. However, its role in CLAD development following lung transplantation remains unknown. Using qRT‐PCR, biopsies from lung transplant recipients with bronchiolitis obliterans syndrome (BOS) demonstrated significant downregulation of LKB1 ( p  = .0001), compared to stable biopsies. To determine the role of LKB1 in EMT development, we analyzed EMT in human bronchial epithelial cell line BEAS‐2B. Knockdown of LKB1 by siRNA significantly dysregulated mesenchymal markers expression in BEAS‐2B cells. Following incubation of human primary bronchial epithelial cell or BEAS‐2B cells with exosomes isolated from BOS or stable lung transplant recipients, LKB1 expression was inhibited when incubated with BOS‐exosome. Incubation with BOS‐exosomes also decreased LKB1 expression and induced EMT markers in air–liquid interface culture method. Our results provide novel evidence that exosomes released from transplanted lungs undergoing chronic rejection are associated with inactivated tumor suppressor gene LKB1 and this loss induces EMT leading to the pathogenesis of CLAD following human lung transplantation. Abstract : Lung transplant recipients with bronchiolitis obliterans syndrome exhibit down regulation of the tumor suppressor gene, liver kinase B1, which, when inhibited by siRNA, induces markers of epithelial mesenchymal transition in vitro. Bos comments on page 689